1992
DOI: 10.1007/bf00302877
|View full text |Cite
|
Sign up to set email alerts
|

New gene in the homologous human 11q13?q14 and mouse 7F chromosomal regions

Abstract: Alterations in the chromosomal region 11q13-11q14 are involved in several pathologies in which most of the key genes remain to be identified. In an effort to isolate as many candidates as possible, we are cloning genes from this region. We report here the mapping of a new sequence from 11q13.5-11q14. This sequence, designated D11S833E, putatively encodes a new gene, provisionally named GARP. We cloned its homologous sequence in the mouse and located it on Chromosome (Chr) 7, region F. The human and mouse genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…The GARP or LRRC32 gene consists of 662 aa and encodes an 80-kDa transmembrane protein with an extracellular region composed primarily of 20 leucine-rich repeats (11,12). As the Garp gene is expressed in multiple cell types in the mouse during embryogenesis, it has been proposed that Garp plays an important role in development, but its actual function is unknown (13).…”
mentioning
confidence: 99%
“…The GARP or LRRC32 gene consists of 662 aa and encodes an 80-kDa transmembrane protein with an extracellular region composed primarily of 20 leucine-rich repeats (11,12). As the Garp gene is expressed in multiple cell types in the mouse during embryogenesis, it has been proposed that Garp plays an important role in development, but its actual function is unknown (13).…”
mentioning
confidence: 99%
“…The major portion of the protein consists of 20 leucine-rich repeat (LRR) domains (Ollendorff et al, 1994). Due to the LRR domains, the GARP protein (Garpin) has structural similarities to other proteins, including chaoptin and connectin, which are involved in the development of sensory organs and the nervous system in Drosophila (Ollendorff et al, 1992). The two amino acid substitutions identified in this study both occur within an LRR domain and may disrupt the tertiary structure of the Garpin protein (Mindrinos et al, 1994;Whitman et al, 1994;Bent et al, 1994).…”
Section: Discussionmentioning
confidence: 81%
“…The GARP gene was first identified and mapped to the region of chromosome 11q13.5-11q14 by Ollendorff et al (1992). Results of the current study place this gene between flanking markers D11S916 and D11S527 in the region of USH1B.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Chromosome 11 has been the focus of attention in many studies of diverse types of malignancies [25,26]. In our study, the observed change in chromosome 1 I in q14/q22 is the location of a new gene named GARP, positioned in the llq14 region [27], and the ataxia-telangiectasia gene located in the 1 1q22-23 region [28,29]. The observed duplication on RHEK tumorigenic cells may be related to the AT gene or another oncogene/tumor suppressor gene in the 11 q14>q22 region responsible for tumorigenicity in radiation-induced squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%